Proteomic analysis of the effects of thioctic acid within meglumine thioctate - I. I. Torshin; O. A. Gromova; O. I. Koifman; L. A. Maiorova (LLC "Publisher OKI", 2017)
Proteomic analysis indicated 6 target proteins of thioctic acid (TA) and 11 proteins of TA metabolism, all of which are mitochondrial proteins. In the structure of the target proteins (namely, P-protein, H-protein, lipoamide acyltransferase, dihydrolipoyline acetyltransferase, X-protein pyruvate dehydrogenase, dihydrolyloylizine succinyltransferase), TA is a cofactor which is covalently bound to specific lysine residues and which is required for processing glycine and other amino acids, thus maintaining the activity of the Krebs cycle. Insufficient activity of these target proteins (due to either genetic defects or nutritional TA deficiency) leads to mitochondrial insufficiency, hyperglycinemia, biliary cirrhosis, "maple syrup urine" syndrome and other metabolic disorders. Insufficient activity of the 11 proteins of TA metabolism is associated with multiple disorders of mitochondrial function, lactic acidosis and anemia. Thus, TA is fundamentally important for supporting the function of mitochondria and of the cellular energy metabolism.